The Ants (Hymenoptera: Formicidae) of Jaragua National Park, Dominican Republic. (2nd September 2014) - Lubertazzi, David; Alpert, Gary D.
Abstract : This study examined ant species richness in Jaragua National Park (Pedernales Province, Dominican Republic). Ants were sampled at 15 sites during late March and early April, 2012. Habitats sampled included dry forest, beach scrub, lakeside acacia scrub, and thorn woodland. Sixty-four species from 23 genera were collected. Species richness was higher than expected, considering only 125 species had previously been reported for all of Hispaniola. Jaragua National Park is part of the Jaragua-Bahoruco-Enriquillo Biosphere Reserve. The ant species richness observed in this study suggests that the park, along with larger reserve, is successful in preserving important habitat for insects.